THE SUBJECT OF PRODUCTION IN A GLOBALIZED WORLD - Papapetropoulos, Petros (European Scientific Journal, ESJ, 2013)
Capitalism is the social production that takes place in private economic units and the contradiction between social and private is resolved by private exchange of goods. Capital, over all, is the manifestation of a social relationship, the disobedience of which manifests itself through the continuous mobility under two aspects: functional transformations, and spatial movements. With the State, exceeded, the articulation of the productive relationship in every point of the economically defined space can interpret the shift from past macroeconomic equilibrium of the national area to the pulse of the open beam free world goods which corresponds to a direct productive meeting between the capital and labor. Developments in both credit and productive field equivalent to an autonomous operation of capitalist relations prepared by the internationalization of the State, and create flexible boundaries that allow potential labor participation in profits. The modern social Meta – organization, selects money as a reflection of the relationship developed in each field of the production of value. As it relativizes the space, this field extends beyond the limits of traditional production relations that are articulated within the place.